Industrial Productivity in Great Britain and the United States - Flux, A. W. (Quarterly Journal of Economics, 1933)
Sources and nature of the data used. The extent of the ground covered, 3.— Numerical comparisons for U. S. (1925) and U. K. (1924), 6. — Arrangement of data for comparison, 7. — Relative importance of chief industrial groups in the two countries, 10.— Variations in net outputs (and in aggregate wages) in relation to numbers occupied, 14.— Some explanations suggested, 15.— Contrast between the U. S. averages and the U. K. 16.—Question whether the larger U. S. figures should be interpreted in terms of higher prices or of greater volume of output, illustrated from various trades, 17.—Differences appear to reflect mainly volume of output, 25.— Movements between the years 1907 and 1924 of the British inquiries considered in relation to U. S. data for 1909 and 1925, 26.— Extension of this comparison to 1930 (U. K.) and 1929 (U. S.), 33.— Differences in time of the inquiries sufficient to account for the major part of the changes in the measure of relative magnitude of output per head, 34.— Some concluding reflections, 37.